Database security - Basta, Alfred (Course Technology / Cengage Learning, 2012)
As a society that relies on technology to thrive, we face a growing number of potentially catastrophic threats to network security daily. DATABASE SECURITY delivers the know-how and skills IT Professionals must have to protect technology infrastructures, intellectual property, and the company's prosperity. From database installation and testing to auditing and SQL Injection, DATABASE this text delves into the essential processes and protocols that prevent intrusions, while reinforcing each topic with eye-opening, real-world examples. Unlike most texts on database security, which take a computer scientist's analytical approach, Database Security focuses on implementation, and was written expressly for the expanding field of Information Technology careers.